Filosofia da agronomia: elementos epistemológicos e tradições de pesquisa. - Albrecht, Leandro Paiola (2024)
The remarkable scientific production in agronomy and its recent technological results, as in other applied sciences, deserve historical attention and philosophical reflection, given its importance in contemporary debates related to hunger, food sovereignty, and environmental sustainability. This thesis investigated epistemological elements of agronomy as a science, given the challenges and solutions imposed in history. The central problem of this thesis proposal focuses on an investigation into agronomy as a science, its development, and competing scientific traditions in the contemporary scenario. In this context, agronomy as a science, the target of this proposal, becomes a problem to be studied, and it is important to answer: What is agronomy? How does knowledge production occur in agronomy? How does the issue of progress and traditions in agronomy arise? To reach these answers, it is important to investigate and reflect on agronomic sciences, their history, how knowledge is produced, how it is organized, how it develops, what traditions are like, what the dynamics of traditions are like, and how they change. In the construction of the theme, the investigation of hypotheses included historical observation and conversation with authors linked to more recent discussions, within the epistemology of agronomic sciences and agrotechnologies, with a historicist perspective of agronomy, when using the philosophy of science of Larry Laudan. Agronomy is proposed to be a solid science in progress based on problem-solving and marked by great scientific and technological achievements, influenced by cognitive values, with different commensurable and competing research traditions, marked by a rational and reticular evolution, of notable social importance and very prolific. The prevalent challenges of agricultural sciences, their moments, their tensions, their evolution, their dramas, and environmental, social, political, economic, and bioethical issues are reasons for intense action and philosophical debate. These provocative scenarios are assumptions and opportunities in the creation of a philosophy of agronomy, for which this work sets out to lay the foundations through a discussion of epistemological elements and research traditions in agronomic sciences.